Inhibiting the alternative pathway of complement by reducing systemic complement factor B: Randomized, double-blind, placebo-controlled phase 1 studies with Sefaxersen - McCaleb, Michael L.; Hughes, Steven G.; Grossman, Tamar R.; Frazer-Abel, Ashley; Jung, Bill; Yin, Lixuan; Henry, Scott P.; Monia, Brett P.; Schneider, Eugene; Geary, Richard; Brice, Gary T. (Immunobiology (1979), 2025)
An over-active alternative complement pathway has been implicated in the pathophysiology of multiple diseases, including IgA nephropathy and geographic atrophy secondary to age related macular degeneration. In first-in-human double-blind, placebo-controlled phase 1 studies, the safety and pharmacodynamic effects of sefaxersen (RO7434656), a GalNAc-conjugated 2’-MOE antisense oligonucleotide targeting the complement factor B mRNA, was investigated. Healthy volunteers received either single or repeated (for 6 weeks) subcutaneous administrations of investigational drug or placebo. Safety and plasma complement protein levels were assessed throughout the studies and during 90-day follow-up periods. All subjects (54) completed the studies and no safety signals or clinically meaningful changes in blood chemistry, urinalysis, hematology, ECG, vital signs or ocular endpoints were observed. Mean levels of systemic complement factor B (FB) were reduced up to 38 % after single administration and 69 % after repeated administration. Lowering of FB protein was paralleled by similar reductions of plasma Bb levels. There was a strong correlation between reduction of plasma levels of FB and alternative complement pathway activity (AH50), but no meaningful changes in classical complement pathway activity (CH50). The long duration of lowering of FB levels following the last dose supports monthly dosing in future clinical trials. These clinical results support the ongoing Phase 2 development for geographic atrophy secondary to age-related macular degeneration and Ph 2/3 development for IgA nephropathy.